Industrial policy and structural transformation: Insights from Ethiopian manufacturing - Kasper Vrolijk (Development Policy Review, 2021)
Motivation The question of industrial policy has gained prominence in the policy agenda over the last decade, despite its persistently ambiguous and incomplete definition. The lack of a firm definition is problematic because it prevents scholars and policy-makers from comparing and monitoring the impact of industrial policy across developing countries. This vague definition also fails to account for issues that are relevant to the impact and usefulness of industrial policy in the process of economic development. Research Question What is the effect of an inadequate definition and implementation of industrial policy for structural transformation in underdeveloped economies? Methods We undertake both a critical literature review of industrial policy and a policy review, and use insights from 86 structured interviews with manufacturing businesses and government officials in Ethiopia, to illustrate how industrial policy could be more effective. Findings The article finds that there is no clear and exhaustive understanding of what the definition of industrial policy entails. In part this is also a result of a limited and incoherent use of the concept of structural transformation in the definition and policy formulation of industrial policy. Conclusions Using a case study of Ethiopia, we show how an inadequate and incoherent definition and implementation of industrial policy can lead to limited upgrading, learning and innovation in an underdeveloped economy. Policy Implications For Ethiopia, and for other underdeveloped economies, the findings imply a reconfiguration of industrial policy, rather than more industrial policy.
Keywords: 300; economic transformation; Ethiopia; global value chains; industrial policy; structural transformation